How gender norms constrain women's economic resilience to climate change challenges in Nigeria - Mudege, Netsayi; Olajumoke, Adeyeye; Kakwasha, Keagan; Muzungaire, Lizzy; Akuwa, Elizabeth (WorldFish, 2023)
This report presents the findings of qualitative assessments conducted on inequitable norms that restrict women’s capacities to build economic resilience to climate change challenges in Nigeria. The study sought to answer the following question: What gender norms prevent women from building economic resilience to climate change challenges in agrifood systems (AFSs), and to what extent do these discriminatory biases exist at different institutional levels?